Jacaranda copaia (Aubl.) D. Don. subsp. spectabilis (Mart. ex A. DC) Gentry (Bignoniaceae): morphological aspects of fruit, seed and seedling - Gurgel, Ely Simone Cajueiro; Santos, João Ubiratan Moreira dos; Carvalho, Ana Cristina Magalhães; Bastos, Maria de Nazaré do Carmo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Jacaranda copaia (Aubl.) D. Don. subsp. spectabilis (Mart. ex A. DC) Gentry is the only species known as Parapará in Amazonian, they occur at the Amazonian firm forests, is distributed in the states of Amazon, Pará, Mato Grosso, Tocantins, Roraima, and part of the states of the south and of the southeast. This wood is used mainly for the civil building. This study object was describing the morphology of the fruit, seed and seedlings, was use 30 fruits, 30 seeds and 10 seedlings. Of the fruits was described the general morphology, coloration, texture, consistence, dehiscent and the indumento; of the seeds the tegument and the embryo and the main vegetative elements of the seedling. Was considered seedling the development phase in that the eophylls were totally formed. The whole study was based in specialized literature and the main morphologic characters were illustrated with pictures. The simple capsule is dries, estenocarpic, elliptic the oblong, dehiscent, green and pericarp opaque, immature and in almost black brown tones, glabrous and chartaceous; opaque, in brown tones, surface glabrous and fibrous; woody funiculus in brown tones. Estenospermic seed, cordiformeou; monocromic testa, in brown tones, opaque, spongy, surface glabrous; hilum close to the apex of the radicule, punctiforme hilum, heterocromy, brown light than the testa, in depression; brown light tegmen and membranaceous; enlarged embryo, axial, foliaceous, invaginate, yellow, cotyledon gross, whitish, dominant, cordiformes, with apex deeply bilobate, margin completes, round base, auriculate with the exposed radicule; embryonic axis among the lobes cotyledonate, straight, conical, thick, pearly; yellows plumule, rudimentary. Fanerocotylar epigeous germination. Seedlings with trifoliolate eophylls, opposed, symmetrical, oval, margin crenate, with hair hialinous and simple for the whole limbo, canaliculate peciolous. The saplings has the second order eophylls imparipinate with five foliolous, and crusade leaf arrangment
Keywords: Forestry management; Silviculture; Seedlings identification; Amazon